Law and the visual: representations, technologies, and critique - Manderson, Desmond (University of Toronto press, 2018)
"In Law and the Visual, leading legal theorists, art historians, and critics come together to present new work examining the intersection between legal and visual discourses. Proceeding chronologically, the volume offers leading analyses of the juncture between legal and visual culture as witnessed from the fifteenth to the twenty-first centuries. Editor Desmond Manderson provides a contextual introduction that draws out and articulates three central themes: visual representations of the law, visual technologies in the law, and aesthetic critiques of law. A ground breaking contribution to an increasingly vibrant field of inquiry, Law and the Visual will inform the debate on the relationship between legal and visual culture for years to come."--